SOCIAL ISSUES in SPORT - Woods, Ronald B., 1943 November 6-; Butler, B. Nalani, 1986- (Human Kinetics, 2021)
"This book examines contemporary sport both factually and critically, particularly in the United States. The book situates the modern sport world in the context of the historical development of sport. It presents the controversies and the status of sport in a sociological context without dwelling on theoretical constructs"--